Modelo Prolab: Edutruck, centros móviles de capacitación y reclutamiento para jóvenes residentes de zonas de bajos recursos de Lima Metropolitana - Sarango Aguirre, Claudia Alejandra (2024)
One of the social problems of our country is the gap in education and decent formal work for low-income young people residing in the peripheries of Metropolitan Lima. The proposed solution to this problem is Edutruck, which are mobile centers where young people receive free training with the aim of inserting them into the formal labor market, starting in the position of warehouse operator. The users are young people between 18 and 24 years old who live in areas close to the logistics centers clusters, and the clients are companies with distribution centers with personnel needs and social responsibility policies to whom the recruitment and selection service would be provided. Edutruck will be located in these strategic areas close to young people and customers. The business model is viable, with an initial investment of S/785,748 and a price of S/1,025 per trained and recruited operator, providing an IRR of 124% and a NPV of S/3,025,738 in a period of 5 years. In addition, the impact metrics, aligned with SDGs 4 and 8, reflect the model's commitment to generating a significant social impact by training 276 students per month. Compared to the competition, Edutruck is an innovative and socially sustainable solution, being a key competitive advantage in its positioning strategy. The detailed implementation plan, which includes market study, financing, constitution and launch in 5 months, reinforces the viability of the project.